Surgical treatment of left-sided infective endocarditis with symptomatic neurological complications before surgery in China - Huang, Jing-bin; Lu, Chang-chao; Wen, Zhao-ke; Yang, Jian-rong; Li, Jun-jun (Frontiers in Cardiovascular Medicine, 2023)
Introduction We aimed to investigate surgical treatment of left-sided infective endocarditis with symptomatic neurological complications before surgery. Methods This was a retrospective study of patients with left-sided infective endocarditis and symptomatic neurological complications before surgery undergoing cardiac surgery between January 2006 and November 2022 at our hospital. Results Eight hundred thirty-two patients were divided into group with symptomatic neurological complications before surgery (n = 112) and without symptomatic neurological complications before surgery (n = 720). There were 48 operative deaths (5.4%). Univariate and multivariate analyses showed that symptomatic neurological complications before surgery is statistically significantly associated with in-hospital mortality following cardiac surgery and prolonged intubation time. Conclusions Our study showed that symptomatic neurological complications before surgery are associated with increased in-hospital mortality following cardiac surgery and prolonged intubation time.